1979
DOI: 10.1007/bf02660239
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in glyceride composition during directed interesterification of lard

Abstract: A detailed study on directed interesterification is presented based on triglyceride group analysis by argentation thin layer chromatography. The process is illustrated by the curves for the changes of six triglyceride groups with different unsaturation using lard as a suitable model fat. The deviation of the triglyceride types away from their theoretical change levels is presented. The influence of the temperature on the rearrangement is examined towards trisaturated and disaturated triglycerides, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
3
1
0
Order By: Relevance
“…The interesterified blend exhibited higher 18:2 and UFA/SFA values than the small-scale blend ( Table 3). Previous researchers reported that a chemically interesterified 60:40 blend of lard and sunflower seed oil exhibited increased saturation, especially in S 2 D, SM 2 , S 2 M, and SMD (where S = saturated acyl, D = diene acyl, and M = monoene acyl) (26). The enzymatically interesterified blends reported here had fatty acid profiles similar to the physical blend.…”
Section: Resultssupporting
confidence: 65%
“…The interesterified blend exhibited higher 18:2 and UFA/SFA values than the small-scale blend ( Table 3). Previous researchers reported that a chemically interesterified 60:40 blend of lard and sunflower seed oil exhibited increased saturation, especially in S 2 D, SM 2 , S 2 M, and SMD (where S = saturated acyl, D = diene acyl, and M = monoene acyl) (26). The enzymatically interesterified blends reported here had fatty acid profiles similar to the physical blend.…”
Section: Resultssupporting
confidence: 65%
“…Any further increase in reaction time had little effect on U 3 TAG yield, as the reaction might have reached its equilibrium state. These findings are in agreement with the findings of Chobanov and Topalova (1979) who reported that U 3 TAG yield in lard increased with a more extended reaction time of EDIE. U 3 TAG yield in lard reached its maximum after approximately 18-20 hr at a reaction temperature of 28°C, with little increase in U 3 TAG yield when the reaction time was extended.…”
Section: Degree Of Three Parameters On Enzymatic Directed Interesterisupporting
confidence: 93%
“…It was observed that an increase in reaction temperature resulted in a modest but significant increase in by-products yield, which is in line with findings of Lee et al (2015) and Mu et al (1998). Mu et al (1998) reported that raising have been reported by Chobanov and Topalova (1979) who found that to obtain a higher U 3 TAG yield from EDIE of lard, EDIE was best carried out at about 28°C. In the case of EDIE of PO, if the reaction was carried out at a temperature higher than 35°C, it will not result in a high yield of U 3 TAG because the high reaction temperature will impede the precipitation of the high melting TAG that were formed during EDIE.…”
Section: Single Factor Responsesupporting
confidence: 86%
“…DIE eventually results in a lipid mixture that contains a high proportion of S 3 and U 3 TAG, at the expense of disaturated (S 2 U) and diunsaturated (U 2 S) TAG (De Lathauwer et al, 1983;Placek and Holman, 1957). DIE increases U 3 and S 3 TAG of lard (Rousseau and Marangoni, 2008;Chobanov and Topalova, 1979), tallow (MacKenzie and Stevenson, 1995) and palm oil (PO) (Lago and Hartman, 1986;Laning, 1985). Chemical DIE increases U 3 and S 3 TAG of PO to 12% and 30%, respectively (Laning, 1985).…”
Section: Lipozyme Tlim Lipase Conditioningmentioning
confidence: 99%